Emotional Experiences Predict the Conversion of Individuals with Attenuated Psychosis Syndrome to Psychosis: A 6-Month Follow up Study - Chen, Fa Zhan; Wang, Yi; Sun, Xi Rong; Yao, Yu Hong; Zhang, Ning; Qiao, Hui Fen; Zhang, Lan; Li, Zhan Jiang; Lin, Hong; Lu, Zheng; Li, Jing; Chan, Raymond C. K.; et al. (Frontiers in Psychology, 2016)
The present study explored the conversion rate in individuals with Attenuated Psychosis Syndrome (APS) and potential predictor for transition in China. Sixty-three participants were identified as APS were followed up six months later. The results showed that 17% of individuals with APS converted to psychosis. The converters exhibited poorer emotional experience and expression than the non-converters at baseline. A further binary logistic regression analysis showed that emotional experience could predict the transition (Wald = 4.18, p = 0.041, 95% CI = 1.04 6.82). The current study suggested an important role of emotional processing in the prediction of the development of full-blown psychosis.